Karakteristik Tepung Premiks Berbahan Terigu dan Tepung Millet (Panicum miliaceum L.) Kecambah-Fermentasi pada Pembuatan Bolu Kukus - Dian Prativi, Regine; Kartika Pratiwi, I Desak Putu; Yusa, Ni Made (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 12 No 1 (2023): Jurnal ITEPA, 2023)
Millet flour produced by germination-fermentation method has been developed as substitute for wheat flour. This study was aimed to find out the characteristics of steamed cake premix flour made from wheat flour and GF millet flour, and to determine the exact ratio between wheat flour and GF millet flour to produce steamed cake with the best sensory characteristics. This research used Complete Randomized Design with a treatment of ratio between wheat flour and millet flour that consisted of 5 levels: 100%:0%, 85%:15%, 70%:30%, 55%:45%, and 40%:60%. The treatment was repeated three times to obtain 15 experimental units. The data obtained were analyzed by analysis of variance, if the treatment had a significant effect, then followed by Duncan Multiple Range Test. The result showed that the ratio between wheat flour and GF millet flour had a significant effect on ash content, fat content, and crude fiber for the premix flour, also had significant effect on swelling power , color intensity (scoring test), softness texture (scoring test), sandy texture (scoring test), texture (hedonic test), and overall acceptance for the steamed cake. The ratio 70:30 of wheat flour and GF millet flour had the best characteristics with moisture content 7.65%, ash content 1.08%, protein content 7.07%, fat content 3.04%, carbohydrate content 81.16%, crude fiber 3.29%, swelling power 153.48%, with sensory characteristics of steamed cake are lighted colors, soft and sandy texture, hedonic for color, aroma, texture, taste, overall acceptance is liked.